A Cross-Sectional Survey on Pharmacists’ Experiences in Engaging with Consumers - Choudhary, Homesh; Koneri, Raju; Ramasamy, Rajeswari (Indian Journal of Pharmacy Practice)
Introduction: This study aimed to evaluate the role of community pharmacists and explore their experiences related to patient trust and satisfaction in urban Northern Bengaluru. Materials and Methods: A descriptive cross-sectional survey was conducted from September to November 2022 using a structured, bilingual questionnaire. It was administered to 145 community pharmacists who consented to participate (response rate: 72.5%) out of 200 approached. The survey captured socio-demographic data and key practice aspects like repeat patient visits, medication counselling practices, patient trust during medical emergencies, comfort in sharing personal health issues, and specific instances of patient appreciation. Results: The majority of respondents were male (71%), diploma-qualified (58.6%), and had over 10 years of experience (71.7%). Most pharmacists (86.2%) were above 30 years of age. A significant 63% reported repeat customer visits, while 72% stated they always provided medication counselling. In emergencies, 89% confirmed that neighbourhood patients approached them first, highlighting their accessibility and community trust. Regarding communication, 60% patients sometimes confide health concerns, and 36% reported frequent disclosure, reflecting trust levels but also signalling the need for improved engagement. Notably, pharmacists shared real-life experiences of patient appreciation, including providing emergency aid, medicine donations, and correcting prescription errors. These accounts reflect their empathetic responsive role, strengthening their position as accessible healthcare providers. Conclusion: The findings highlight the growing role of community pharmacists in patient-centred care and emergency response. High levels of patient revisit, trust, and appreciation indicate that pharmacists are vital healthcare touchpoints. However, gaps in formal clinical education and communication training persist. Strengthening continuing education programs with structured communication and patient engagement modules is essential to enhance their impact and support the evolving expectations of modern pharmacy practice.
Keywords: Community Pharmacist; Patient Trust; Medication Counselling; Cross-sectional Study; Primary Healthcare; Bengaluru